1965
DOI: 10.1111/j.1365-2672.1965.tb02166.x
|View full text |Cite
|
Sign up to set email alerts
|

The Identification, Epidemiology and Pathogenicity of the Salmonellae of Subgenus II

Abstract: A short description of the biochemical criteria used in the differentiation of the salmonellae of subgenera I, I1 and Arizona is given. Important antigenic differences have been found between the subgenera I and 11. The pathogenicity and epidemiology of subgenus 1 1 are discussed. In 1960 Kauffmann proposed dividing the salmonellae on the basis of certain fementative differences into two biochemically defined subgenera. This subdivision is useful and is already carried out in a number of laboratories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…S.11 serotypes are regarded as an uncommon cause of disease in man (Rohde, 1965;Farmer et al 1984), a view that is supported by retrospective analysis of the serotypes reported in a number of surveys published over the last three decades. Only 3 isolates of a single S.II serotype were reported among 3216 salmonellae cultured from humans before 1960 in Central Africa (the former Belgian Congo and Ruanda-Urundi).…”
Section: Methodsmentioning
confidence: 96%
“…S.11 serotypes are regarded as an uncommon cause of disease in man (Rohde, 1965;Farmer et al 1984), a view that is supported by retrospective analysis of the serotypes reported in a number of surveys published over the last three decades. Only 3 isolates of a single S.II serotype were reported among 3216 salmonellae cultured from humans before 1960 in Central Africa (the former Belgian Congo and Ruanda-Urundi).…”
Section: Methodsmentioning
confidence: 96%
“…enterica (Rohde 1965;Popoff and Le Minor 1992). Most retrospective studies have confirmed their rare occurrence in humans; thus, only 27 isolates of serotypes of subsp.…”
Section: Subspecies IImentioning
confidence: 99%
“…Central Africa before 1960 (see Schrire et al 1987), Malaysia 1973-82 (Jegathesan 1984 and France 1980-83 (Le Minor et al 1985. The main reservoirs of this subspecies are healthy or diseased reptiles and diverse coldblooded animals (Rohde 1965). …”
Section: Subspecies IImentioning
confidence: 99%